EFFECTS OF PRE AND POST CONSOLIDATION POLICY IN NIGERIAN BANKS ON AGRIBUSINESS SECTOR PERFORMANCE (1995-2014): A COMPARATIVE ANALYSIS - Joseph ONWUMERE; Chinonso Henry ENE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This study is a comparative analysis of the effects of pre and post-consolidation policy in Nigerian banks on agribusiness sector performance which covered 1995-2014 periods. Secondary data from CBN annual reports and statement of accounts, CBN bulletin and National Bureau of Statistics were used for the study. The data were analyzed by the use of t-students distribution. This paper used agribusiness output, number of agribusiness entrepreneurs that accessed the credits, government credit allocation to agribusiness and value of banks' credit allocation to agribusiness as indices to determine agribusiness sector performance by comparing the pre-mergers and acquisition consolidation policy with the post-merger and acquisition consolidation policy for the period under review. Findings shown that the purposes for credit allocation among agribusiness sub-sectors in the pre and post-merger and acquisition consolidation policy in the Nigerian banking institutions were mainly for the production of crop, livestock, fishery, mixed farming and others. In the post-merger and acquisition consolidation policy era, number of agribusiness farmers that accessed the credit through Agricultural Credit Guaranteed Scheme Fund (ACGSF), government credit to agribusiness enterprises, value of banks' credit to agribusiness, agribusiness output was higher than the pre-merger and acquisition consolidation era of Nigerian banking institutions. The study concluded that consolidation policy in the Nigerian banking institutions influenced the agribusiness sector performance. It was recommended that efforts must be made by the Central Bank of Nigeria to see that such policy is sustained.